MOTIVASI ORGANISASI DAN KOMITMEN ORGANISASI UKM PADUAN SUARA MAHASISWA DI SURABAYA - Ressy Mardiyanti; Aprilia Dian Eky Anggraini (PSIKOWIPA (Psikologi Wijaya Putra), 2022)
In every university there is always a student activity unit (UKM) that can be followed to hone non-academic abilities such as talent, communication, social relations and much more. Each student has various interests and goals to participate in various types of SMEs in higher education. When you have chosen to join one of the UKM, there must be a demand for commitment and encouragement to organize, as well as the choir UKM members at Wijaya Putra University. However, this has not been seen in the members of the UWP choir UKM, for example, it is very rare for members to take part in routine training, work meetings, and many do not carry out their responsibilities when given the authority of the committee. The purpose of this study was to determine whether there is an influence between organizational motivation and commitment in choir SMEs. This research is a quantitative study, using the Wilcoxon test, because the data are not normally distributed with the help of SPSS 21. The results show a sig value of 0.000 <0.05, which means that there is an influence of organizational motivation on organizational commitment to members of the Wijaya Putra University Choir UKM